Rastreamento de escoliose em crianças e adolescentes com Encefalopatia crônica - Santos, Lucicleia Nascimento (Brasil, 2021)
Introduction: Chronic infantile encephalopathy (ECI) or cerebral palsy (CP) is a nongradual encephalic disease, caused by brain damage in the first stage of its evolution, resulting in permanent motor impairment. The vertebral deformity in a patient with encephalopathy has a multifactorial cause, muscle weakness, spasticity and inefficient muscle control. Objective: Assess head and trunk control during static and dynamic activities. Methods: This is a convenience sample, composed of individuals aged 3 to 15 years old, with confirmed or open diagnosis for ECI residing in the city of Coari - AM and attended at the Physiotherapy School Clinic of the Instituto de Saúde e Biotechnology at the Federal University of Amazonas (IBSUFAM). Results: The correlation between the angle of rotation of the trunk and the balance of the trunk showed that the higher the balance, the angle of rotation decreases, rather than increased. On the other hand, the higher the angle of rotation of the trunk, the worse the balance of the individuals. Thus, the correlation values were considered low (Cervical: R=-0.07; Thoracic: R=-0.3; Lumbar: R=-0.4). Conclusion: Therefore, in relation to scoliosis screening, lumbar spine angulation values:R=0.4 had a significant correlation in most individuals showing lumbar scoliotic deviation in addition to a deficit in trunk balance affecting its functionality.